Comprehensive analysis and experimental validation of five-level converters for ev battery chargers framed in smart grids - Monteiro, Vítor Duarte Fernandes (2019)
The electric vehicle (EV) is the foremost element for spreading electric mobility in smart grids. Its integration into the electrical power grid involves the use of battery chargers with improved power quality aspects, and therefore, the topology of the front-end power converter represents a vital role in the EV battery charger (EVBC). Since multilevel topologies offer a set of advantages to accomplish with the power grid interface, a comprehensive investigation of two five-level topologies for EVBCs is presented in this paper. An accurate computational validation and a meticulous explanation of the hardware and software required for the five-level topologies under study is presented and explained considering realistic operating conditions. The obtained results show the pros and cons of each topology targeting EVBC applications for smart grids.